Laporan Keberlanjutan yang Berkualitas: Peran Stakeholder Pressure dan Corporate Governance - Mulyaji Dharmawan; Andy Setiawan (Jurnal Eksplorasi Akuntansi, 2024)
This is a quantitative research aimed at examining the influence of stakeholder pressure using the mechanisms of employees and shareholders, as well as corporate governance using the mechanisms of the board of commissioners and audit committees on the quality of sustainability reports. The study sample comprises 35 non-financial sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2018-2021. Secondary data from annual reports and sustainability reports accessible through the Indonesia Stock Exchange website and related entity websites were used in this research. The study employs a random effect model with panel data regression, and data processing was conducted using STATA version 16. Based on the test results, it was found that one variable of corporate governance mechanism, which is the Audit Committee, has a significant positive impact on the quality of sustainability reports. However, the Board of Commissioners did not exhibit a significant influence. As for the stakeholder mechanisms of Employees and Shareholders, they did not demonstrate a significant impact on the quality of sustainability reports.